High-order Harmonic Field Retrieval in Ethylene - Makhija, Varun; Tross, Jan; Kumarappan, Vinod; Spanner, Michael; Vozzi, Caterina; Trallero, Carlos; Stagira, Salvatore (My University, 2019)
The XUV field emitted by impulsively aligned ethylene molecules during high-order harmonic generation is retrieved as a function of molecular orientation. The results can be ascribed to multielectron contributions to the harmonic emission.